PENGEMBANGAN SISTEM INFORMASI KEPENDUDUKAN KECAMATAN KARYA PENGGAWA BERBASIS WEB - Anie Rose Irawati; Dwi Sakethi; Alpiyan Zakki (Jurnal Komputasi, 2015)
Citizen data record can be shown satistically such as according to family number, education, religion, gender, occupation and age group. Tabulation system of demography data used by Karya Penggawa subdistrict is still in manual method such as recording amount of citizen data on Ms. Office Excel. Constraint of using this citizens data record are difficult to get accurate information about citizens data, consume too much time to check the report of citizen data, in other word tabulation of demography data still not optimal yet.By those constraint, then the information system of demography of Karya Penggawa subdistrict is needed. The system is a web based system with the main function is to form tabulation of demography which is able to show statistic of citizens data according to gender, education, occupation, religion and age group on graphics. In addition, the system able to make quarterly report of demography by choosing one of report format Print, PDF, Excel to minimize human error and make the work of staff of Karya Penggawa subdistrict easier in processing of demography.Keywords: Demography, Â Information, Karya Penggawa, Subdstrict, System, Web